CORONARY STENT COATED WITH MESENCHYMAL STEM CELLS-ANGIOGENIC GROWTH FACTOR SEBAGAI AGEN REENDOTELIALISASI DAN PENCEGAHAN RESTENOSIS - Pramartha, I Nyoman Tri; Narayana, Gede Setula; Suryaningsih, Ni Putu Elsinthia (Essential: Essence of Scientific Medical Journal, 2020)
ABSTRACT   Introduction: acute myocardial infarction (IMA) is the caused of medical emergencies with around 17.9 million global deaths. There are various factors associated such as unhealthy food dietary like high fat diet, sedentary lifestyle, smoking and alcohol. The pathogenesis of IMA begins with the formation of lesions atherosclerotic plaque that caused in decreased O 2 perfusion (ischemia) and nutrition resulting in cardiomyocyte necrosis (infarction). The main treatment for overcoming IMA nowdays is percutaneous coronary intervention (PCI) using bare metal stents (BMS) with the disadvantage of achieving up to 50% restenosis. Innovations using drug eluting stent (DES) have not been efficient and led to restenosis and low reendothelization processes. New modalities that tends to have a better effect needed to increase reendothelization and prevent restenosis. Discussion: the construction of coronary stents coated with mesenchymal stem cells (MSC) angiogenic growth factors begins with the formation of MSC culture and then using the TALEN system inserted plasmids containing HGF-VEGF gene. Then implanted in the CoCr stent and ready to be administrated. The resulting work effect is accelerating reendothelization through the proliferation and differentiation of MSC and strengthening the intima tunica by increasing the formation of tight junctions between epithelium. In addition, the effects taken in restenosis. This prevention is caused by immunomodulators and anti-inflammatory effects provided by angiogenic growth factors and induction of autophagi, thus recycling cell nutrients in atherosclerotic lesions. Conclusion: the use of coronary stents coated with mesenchymal stem cell (MSC) angiogenic growth factors is needed as the latest IMA therapy with endothelial acceleration through the proliferation and differentiation of MSC and ancestral cells and the use of restenosis replacement through the use of antibacterial and nutrient recycling.